Analysis for lipid nutrient differences in the milk of 13 species from a quantitative non-targeted lipidomics perspective - Yanzhi Wu; Yinggang Sun; Rui Chen; Yanjun Qiao; Qiu Zhang; Qian Li; Xiaowei Wang; Yuan Pan; Siyi Li; Zeying Wang (Food Chemistry: X, 2023)
Lipids are essential organic components in milk and have been associated with various health benefits for newborns. However, a comprehensive analysis of lipid profiles across multiple species and levels has been lacking. In this study, we employed liquid chromatography-tandem mass spectrometry (LC-MS/MS) to accurately determine the absolute content of lipid molecules. It revealed that ruminants exhibit a higher concentration of short-chain fatty acids compared to non-ruminants. Additionally, we identified ALC (camel), MGH (horse), and DZD (donkey) as species that display similarities to components found in human milk fat. Remarkably, it reveals that porcine milk fat is characterized by long chain lengths, low saturation, and a high proportion of essential fatty acids. PS (22:5_18:2) could potentially serve as a biomarker in porcine milk. These unique characteristics present potential opportunities for the utilization of porcine milk. Overall, our findings provide valuable insights into the lipidomics profiles of milk from different species.